The functional syndrome: linking individual trait variability to ecosystem functioning. Issue 1868 (6th December 2017) - Raffard, Allan; Lecerf, Antoine; Cote, Julien; Buoro, Mathieu; Lassus, Remy; Cucherousset, Julien
Abstract : Phenotypic variability is increasingly assessed through functional response and effect traits, which provide a mechanistic framework for investigating how an organism responds to varying ecological factors and how these responses affect ecosystem functioning. Covariation between response and effect traits has been poorly examined at the intraspecific level, thus hampering progress in understanding how phenotypic variability alters the role of organisms in ecosystems. Using a multi-trait approach and a nine-month longitudinal monitoring of individual red-swamp crayfish ( Procambarus clarkii ), we demonstrated that most of the measured response and effect traits were partially stable during the ontogeny of individuals. Suites of response and effect traits were associated with a response syndrome and an effect syndrome, respectively, which were correlated to form a functional syndrome. Using a bioenergetic model, we predicted that differences in the response syndrome composition of hypothetical populations had important ecological effects on a key ecosystem process (i.e. whole-lake litter decomposition) to a level similar to those induced by doubling population size. Demonstrating the existence of a functional syndrome is likely to improve our understanding of the ecological impacts of phenotypic variation among individuals in wild populations across levels of biological organization, and the linkage between ecosystem and evolutionary ecology.